Peran work-family conflict terhadap organizational citizenship behavior pada karyawan PT. X - Rr. Ratih Purnami Sudrajad; Hudaniah Hudaniah (Cognicia, 2021)
Organizational citizenship behavior is a worker’s behavior that exceeds their role and can benefit the company. In generating OCB, sometimes employees experience various obstacles, one of which is work-family conflict. WFC is a situation where employees have conflicts in carrying out their roles to complete their work with their roles in the family. This study aims to determine the effect of WFC on the emergence of employee OCB. The importance of this research is that the company can pay more attention to its employees in reducing role conflict, and is expected to increase employee OCB. The sampling technique used is purposive sampling. The research subjects were 171 people consisting of permanent employees and they were married. The data collection method used a work-family conflict scale that had been compiled by Carlson et al. and an organizational citizenship behavior scale that had been compiled by Smith et al. A simple regression analysis test with IBM Statistic 25 program showed a significant and negative influence between WFC on employee OCB. Work-family conflict itself contributes an effective contribution of 17.1% to employees’ organizational citizenship behavior.   Keywords: Employees, organizational citizenship behavior, work-family conflict